International migration of entrepreneurs and the emergence of economic development traps. Issue 1 (19th May 2020) - Fan, Zhaobin; Anwar, Sajid
Abstract: This paper examines the link between the emigration of entrepreneurs and the emergence of economic development traps, which has not received much attention in the existing literature. We develop a theoretical model, where the economy is divided into a traditional and a modern sector. Entrepreneurs establish firms in the modern sector to produce varieties of differentiated goods. Positive spillover effects exist in the modern sector. We show that the emigration of entrepreneurs can cause economic development traps, where the productivity of the modern sector remains low, and more importantly, the economy is stuck in the traditional structure. In the typical case, the development traps exhibit strong history dependence. Under certain conditions, regardless of the initial endowment of entrepreneurs, economic development traps are unavoidable. By examining the effect of government policy intervention to correct the market failure arising from spillover effects, our study also provides a theoretical foundation for government policies used by some developed countries to attract foreign entrepreneurs.